Functionalized Fiber Optics for Glucose Detection. (April 2020) - Multar, E.; Daud, S.; Rohizad, S. N. A.; Tan Halid, N. S.
Abstract: Tapered optical fiber immobilized with glucose oxidase (GOD) has been proposed for glucose recognition. Single mode fiber (SMF) is fabricated by tapering using flame-brushing technique to improve the sensitivity and limit of detection of optical fiber based glucose sensor. Taking the benefits from the free amine groups in 3-aminopropyltriethoxysilane (APTES), the enzyme, GOD are functionalized on the tapered region of SMF through covalent interaction. The pH value of the immobilized enzyme, GOD is the critical parameter for glucose sensing. The lower pH value of buffer solution, which is pH3 shows the highest intensity which is 2949.08 compared with intensity peak of pH5 and pH7 which is 2873.9 and 2700.43 respectively.